Composite negative electrode material of carbon nanotube confined encapsulating nanosilicon and preparation method and use thereof
Patent Information
- Application Number
- CN202611043911.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-30
AI Technical Summary
[0078](1)本发明提供的碳纳米管限域封装纳米硅的复合负极材料采用多种沉积技术将纳米硅颗粒沉积封装在碳纳米管内部空腔中,实现了纳米硅颗粒在碳纳米管内部空腔的均匀沉积与致密封装,从根本上改变了硅与碳管复合方式,充分利用碳纳米管的内部空腔缓冲硅颗粒的体积膨胀,避免硅颗粒粉化与电极结构破坏。
Smart Images

Figure CN123002831A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anode material preparation technology, and in particular to a composite anode material of carbon nanotube-encapsulated nano-silicon, its preparation method and applications. Background Technology
[0002] The relatively low theoretical specific capacity of traditional graphite anode materials (approximately 372 mAh / g) has become a key bottleneck in improving the energy density of lithium-ion batteries. Silicon (Si)-based materials, on the other hand, offer advantages due to their extremely high theoretical specific capacity (approximately 4200 mAh / g) and moderate delithiation potential (approximately 0.4 V vs. Li / Li). + With its advantages such as abundant natural reserves, it is regarded as the most promising next-generation high-capacity anode material.
[0003] However, silicon materials face two major challenges in their commercial application: 1. Huge volume effect: During charging and discharging, silicon undergoes alloying / dealloying reactions with lithium, resulting in volume expansion and contraction of over 300%. This drastic volume change repeatedly disrupts the integrity of the electrode structure, causing active material to detach from the current collector and leading to continuous rupture and regeneration of the solid electrolyte interphase (SEI) film, constantly consuming electrolyte and active lithium, ultimately resulting in a sharp decline in battery capacity and a shortened cycle life. 2. Low intrinsic electronic conductivity: Silicon itself has poor conductivity, limiting its rate performance and resulting in poor capacity utilization during charging and discharging at high current densities.
[0004] To overcome these shortcomings, the most common strategy is to construct silicon-carbon (Si / C) composite materials. By dispersing nano-sized silicon particles within a carbon matrix, the carbon matrix can buffer the volume expansion of silicon and improve the overall conductivity of the material. However, traditional carbon matrices have limited mechanical strength, and repeated expansion and contraction of silicon can easily cause them to break and fail, thus losing their protective function for the core silicon. Although the design of carbon coating layers can later compensate for the shortcomings of carbon matrices, the additional inactive materials introduced by the carbon matrix and coating layers reduce the overall mass and volumetric specific capacity of the anode material, which is detrimental to further improving the energy density of the battery.
[0005] Carbon nanotubes have garnered widespread attention and application in the field of silicon-carbon composite materials due to their unique hollow cavity structure, high specific surface area, and excellent electrical conductivity and mechanical properties. In existing technologies, the application of carbon nanotubes in silicon-carbon materials mainly includes using carbon nanotubes as a framework and depositing nano-silicon on the surface of carbon nanotubes.
[0006] CN113860288A discloses a technique for encapsulating nano-silicon powder and cobalt salt in phenolic resin, followed by high-temperature carbonization and growth of carbon nanotubes. However, this technique suffers from problems such as easy agglomeration of silicon particles, difficulty in controlling reaction sites, and poor product consistency. CN202511006156.5 discloses a silicon-carbon co-deposition technique using carbon nanotubes as seed crystals, which improves the transport bottleneck to some extent. However, in this technique, silicon particles are only deposited on the surface of carbon nanotubes, without utilizing the internal cavities of the carbon nanotubes, and there is still room for improvement in the volume effect buffering capacity.
[0007] Despite the progress made in existing silicon-carbon composite technology, there are still four technical challenges: First, silicon particles have poor dispersion and are prone to agglomeration, leading to localized volume expansion and damage to the material structure; second, the interfacial bonding between carbon nanotubes and silicon particles is weak, resulting in discontinuous electron transport paths and limited rate performance; third, the cavity structure of carbon nanotubes is not fully utilized, resulting in limited volume effect buffering; and fourth, carbon nanotubes themselves are prone to agglomeration, leading to a decrease in overall deposition efficiency.
[0008] Therefore, in order to solve the above-mentioned technical problems, providing a silicon-carbon composite anode material with high silicon particle dispersion, strong interfacial bonding between carbon nanotubes and silicon particles, small volume expansion, high electrochemical stability and excellent cycle performance, and its preparation method has become an urgent problem to be solved. Summary of the Invention
[0009] To address the aforementioned technical problems, the present invention aims to provide a composite anode material with carbon nanotube-encapsulated nano-silicon, its preparation method, and its applications. This composite anode material with carbon nanotube-encapsulated nano-silicon utilizes the excellent mechanical properties of carbon nanotubes to buffer the volume expansion of nano-silicon particles, constructing a structurally stable and highly efficient lithium-ion conductive composite system. This achieves an optimized balance between the proportion of inactive materials and battery energy density, providing a new technical path for the design of high-energy-density lithium-ion battery anode materials.
[0010] To achieve this objective, the present invention adopts the following technical solution:
[0011] In a first aspect, the present invention provides a method for preparing a composite anode material of carbon nanotube-encapsulated nano-silicon, the method comprising the following steps:
[0012] (1) The double-pass alumina template is heated to the first reaction temperature under an inert atmosphere, and then carbon source gas is introduced to carry out the first reaction, so as to obtain an alumina template with arrayed carbon nanotubes grown inside the tube.
[0013] (2) Heating an alumina template with arrayed carbon nanotubes growing inside the tube to obtain open carbon nanotubes;
[0014] (3) Place the open carbon nanotubes in the etching solution and etch away the alumina template to obtain positive carbon nanotubes;
[0015] (4) Silicon nanoparticles are deposited into the interior of positive carbon nanotubes by gas-phase method and / or liquid-phase method to obtain carbon nanotubes with deposited silicon;
[0016] (5) Carbon source gas is introduced into the carbon nanotubes containing silicon to perform carbon deposition, thereby obtaining the composite anode material of nano-silicon confined by the carbon nanotubes.
[0017] The composite anode material of carbon nanotube-encapsulated silicon nanoparticles provided by this invention uses a variety of deposition techniques to deposit and encapsulate silicon nanoparticles in the internal cavity of carbon nanotubes. This achieves uniform deposition and tight encapsulation of silicon nanoparticles in the internal cavity of carbon nanotubes, fundamentally changing the silicon-carbon nanotube composite method. It makes full use of the internal cavity of carbon nanotubes to buffer the volume expansion of silicon particles and avoid silicon particle pulverization and electrode structure damage.
[0018] This invention first employs a dual-channel alumina template combined with CVD vapor deposition technology to grow an array of carbon nanotubes within an alumina template tube. The dual-channel alumina template itself possesses certain catalytic activity, catalyzing the growth of carbon nanotubes. Upon termination of carbon nanotube growth, the alumina template deactivates, resulting in the formation of amorphous carbon that accumulates at both ends of the carbon nanotubes. Therefore, the grown carbon nanotubes need to be perforated. By briefly heating the carbon nanotubes containing the alumina template in air, the amorphous carbon can be preferentially oxidized, removing any potential deposits at the ends of the carbon nanotubes. An amorphous carbon layer is applied to the top, while the carbon nanotubes remain stable at this temperature, thus allowing the CNTs to have open cavities and obtaining open-pore positive carbon nanotubes containing alumina. Then, the external alumina template is removed by etching with a low-concentration etching solution, and after washing and drying, positive carbon nanotubes are obtained. Then, nano-silicon particles are uniformly deposited into the interior of the positive carbon nanotubes using a gas-phase method and / or a liquid-phase method, taking advantage of the confinement effect inside the tube. After that, carbon is deposited at both ends of the carbon nanotubes to obtain ordered carbon nanotubes filled with nano-silicon and closed at both ends.
[0019] Furthermore, the reason why the liquid phase method of this invention can deposit nano-silicon into the inner cavity of carbon nanotubes is that during the acid etching of the alumina template, the outer wall of the carbon nanotube becomes hydrophilic to a certain extent, but the inner surface of the carbon nanotube is oleophilic. Since the silicon source liquid is generally soluble in organic solvents, it will selectively enter the interior of the carbon nanotube. Moreover, by utilizing the strong capillary siphon effect of the carbon nanotube, the liquid silicon source will preferentially and rapidly enter the interior of the carbon nanotube, while only a small amount of surface adhering to the outside of the tube will remain. After being coated with a carbon layer, the impact is minimal.
[0020] The “aligned carbon nanotubes” (also known as vertically aligned carbon nanotubes, or VACNTs or CNT Forest) described in this invention refer to a special structure with open ends, in which carbon nanotubes grow in a double-channel constrained substrate with a uniform tube axis and precisely controllable dimensions.
[0021] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. The technical objectives and beneficial effects of the present invention can be better achieved and realized through the following preferred technical solutions.
[0022] In some embodiments, the gas phase method in step (4) specifically includes the following steps: the positive carbon nanotubes are heated to the second reaction temperature under an inert atmosphere, and then a silicon source gas is introduced to carry out the second reaction to obtain carbon nanotubes with deposited silicon.
[0023] In some embodiments, the second reaction temperature in step (4) is 450℃-700℃, for example, it can be 450℃, 480℃, 500℃, 520℃, 550℃, 580℃, 600℃, 620℃, 650℃, 680℃ or 700℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0024] In some embodiments, the silicon source gas includes silane gas and inert gas in a volume ratio of (5-50):(95-50), such as 5:95, 10:90, 15:85, 20:80, 25:75, 30:70, 35:65, 40:60, 45:55 or 50:50, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0025] This invention further controls the volume ratio of silane gas to inert gas to be (5-50):(95-50). The volume ratio of silane gas affects the size and distribution of silicon nanoparticles and the deposition efficiency. If the volume ratio of silane gas is too large, the cracking reaction will be too violent, the size of the silicon nanoparticles will increase significantly, causing particle aggregation and blockage, which will seriously affect the uniformity of silicon nanoparticle distribution, ultimately causing deformation of carbon nanotubes and even damaging the structure of carbon nanotubes. If the volume ratio of silane gas is too small, it will seriously affect the deposition efficiency of silicon nanoparticles. The number of silane molecules participating in the reaction per unit time is limited, resulting in a very slow deposition rate of silicon nanoparticles. In addition, too low a concentration is not conducive to the formation of enough initial crystal nuclei, resulting in sparse silicon particles distributed on the carbon nanotubes.
[0026] In some embodiments, the silane gas includes any one or a combination of at least two of silane, silane, methylsilane, or trichlorosilane. Typical but non-limiting combinations include combinations of silane and silane, silane and methylsilane, methylsilane and trichlorosilane, silane and trichlorosilane, silane and trichlorosilane, silane, silane and methylsilane, silane, methylsilane and trichlorosilane, and silane, silane, methylsilane and trichlorosilane.
[0027] In some embodiments, the flow rate of the silicon source gas is 5 sccm-100 sccm, for example, it can be 5 sccm, 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm or 100 sccm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0028] This invention further controls the flow rate of the silicon source gas to 5 sccm-100 sccm. The flow rate of the silicon source gas affects the nucleation and distribution in the gas phase. If the flow rate of the silicon source gas is too high, it will aggravate the nucleation in the gas phase, resulting in uneven distribution of nano-silicon. An excessively high flow rate means a higher reactant concentration. In the high-temperature pyrolysis zone, the probability of silane molecule collisions increases significantly, easily forming silicon atom clusters or even nano-silicon particles directly in the gas phase. This blocks the ports or pores of the carbon nanotubes, hindering the subsequent entry of silane into the tubes for effective filling, resulting in uneven distribution of nano-silicon particles. If the flow rate of the silicon source gas is too low, the partial pressure of silane in the main gas phase is very low, which is insufficient to drive enough silane molecules to diffuse into the deep pores of the carbon nanotubes at the bottom of the array, making it impossible for nano-silicon to be evenly distributed inside the carbon nanotubes.
[0029] In some embodiments, the time for the second reaction is 5 min to 30 min, for example, it can be 5 min, 10 min, 15 min, 20 min, 25 min or 30 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0030] In some embodiments, the liquid phase method in step (4) specifically includes the following steps: mixing positive carbon nanotubes and silicon source liquid, performing ultrasonic impregnation, and then performing pyrolysis at 300℃-500℃ to obtain carbon nanotubes with deposited silicon.
[0031] The pyrolysis temperature is 300℃-500℃, for example, it can be 300℃, 320℃, 350℃, 380℃, 400℃, 420℃, 450℃, 480℃ or 500℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0032] The silicon source liquid comprises any one or a combination of at least two of cyclopentane, polysilane, silicon tetrachloride, phenyltriethoxysilane, methyl orthosilicate, or alkoxysilane. Typical but non-limiting combinations include combinations of cyclopentane and polysilane, combinations of cyclopentane and silicon tetrachloride, combinations of cyclopentane and phenyltriethoxysilane, combinations of cyclopentane and methyl orthosilicate, combinations of cyclopentane and alkoxysilane, combinations of polysilane and silicon tetrachloride, combinations of polysilane and phenyltriethoxysilane, combinations of polysilane and methyl orthosilicate, combinations of polysilane and alkoxysilane, combinations of silicon tetrachloride and phenyltriethoxysilane, combinations of silicon tetrachloride and methyl orthosilicate, combinations of silicon tetrachloride and alkoxysilane, combinations of phenyltriethoxysilane and methyl orthosilicate, combinations of methyl orthosilicate and alkoxysilane, and combinations of phenyltriethoxysilane and alkoxysilane.
[0033] The mass of the silicon source liquid accounts for 5wt.%-30wt.% of the positive carbon nanotubes, for example, it can be 5wt.%, 10wt.%, 15wt.%, 20wt.%, 25wt.% or 30wt.%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0034] This invention further controls the mass of the silicon source liquid to be 5wt.%-30wt.% of the positive carbon nanotubes. The mass ratio of the silicon source liquid affects the silicon loading and the uniformity of dispersion within the carbon nanotubes. If the mass of the silicon source liquid is too large, the nano-silicon will severely agglomerate, forming large silicon particles that will eventually block the pores and even damage the carbon nanotubes. At the same time, excessive silicon deposition will produce a huge volume effect, which is easy to fall off from the surface of the carbon nanotubes during charge and discharge, resulting in a decrease in cycle stability. If the mass of the silicon source liquid is too small, the silicon loading will be insufficient, and the improvement in the capacity and other properties of the composite material will be very limited, failing to achieve the expected goals.
[0035] In some embodiments, the alumina template in step (1) has channels with a diameter of 10nm-20nm and a thickness of 5μm-25μm. For example, the diameter can be 10nm, 12nm, 15nm, 18nm or 20nm, but is not limited to the listed values. Other unlisted values within the range are also applicable. For example, the thickness can be 5μm, 10μm, 15μm, 20μm, 23μm or 25μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0036] In-situ carbon nanotubes (CNTs) are grown within the pores of an alumina template, with only one CNT growing in each pore. The pore size and thickness of the alumina template determine the size of the CNTs; the pore size determines the diameter, and the thickness determines the length. Alumina template pore sizes are typically chosen to be 10 nm–20 nm to construct higher-diameter multi-walled CNTs; alumina template thicknesses are typically chosen to be 5 μm–25 μm to construct CNTs of corresponding lengths.
[0037] The dual-channel alumina template used in this invention has inherent catalytic activity, eliminating the need for a catalyst. Compared to existing methods that require a catalyst, this invention offers the following advantages: ① It can catalyze the cracking of acetylene to grow carbon nanotubes at relatively low temperatures such as 600℃, while adding a metal catalyst typically requires higher temperatures (usually >700℃) to activate its catalytic activity and promote carbon nanotube graphitization; ② The carbon nanotubes obtained without a metal catalyst in this application can precisely replicate the shape and size of the template channels, resulting in highly consistent orthogonal carbon nanotubes; ③ The carbon nanotubes grown without a catalyst do not contain metal impurities and can be directly processed after CVD growth, eliminating the need for purification steps such as acid washing. In contrast, products with added catalysts must be purified to remove catalyst particles, which increases the complexity and cost of the process.
[0038] In some embodiments, the first reaction temperature is 600℃-900℃, for example, it can be 600℃, 650℃, 700℃, 750℃, 800℃, 850℃ or 900℃, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0039] In some embodiments, the inert atmosphere includes high-purity nitrogen and / or argon.
[0040] In some embodiments, the carbon source gas includes any one or a combination of at least two of acetylene, ethylene, methane, or toluene vapor. Typical but non-limiting combinations include combinations of acetylene and ethylene, ethylene and methane, methane and toluene vapor, acetylene and methane, ethylene, methane, and toluene vapor, acetylene, ethylene, and toluene vapor, and acetylene, ethylene, methane, and toluene vapor.
[0041] In some embodiments, the flow rate of the carbon source gas is 10 sccm-100 sccm, for example, it can be 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm or 100 sccm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0042] In some embodiments, the time for the first reaction is 10 min to 60 min, for example, it can be 10 min, 15 min, 20 min, 30 min, 40 min, 50 min or 60 min, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0043] In some embodiments, the heating temperature in step (2) is 300℃-450℃, for example, it can be 300℃, 320℃, 350℃, 380℃, 400℃, 420℃ or 450℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0044] In some embodiments, the heating time is 1-3 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0045] In some embodiments, the heating atmosphere is an oxygen-containing atmosphere, such as an air atmosphere and / or an oxygen atmosphere.
[0046] In some embodiments, the etching solution in step (3) includes an acid solution or an alkaline solution.
[0047] In some embodiments, the acid solution includes hydrochloric acid solution and / or sulfuric acid solution, and the alkaline solution includes sodium hydroxide solution.
[0048] In some embodiments, the mass fraction of the acid solution is 10%-50%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0049] In some embodiments, the concentration of the alkaline solution is 0.01 mol / L to 0.2 mol / L, for example, it can be 0.01 mol / L, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.18 mol / L or 0.2 mol / L, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0050] This invention involves etching an alumina template using dilute acids and / or dilute alkalis. Since alumina is an amphoteric oxide, both acids and alkalis essentially convert the solid alumina into soluble aluminum ions (Al). 3+ ) or aluminate ions (AlO2) -Then, it is removed from the system by washing. Low concentrations of acid / base effectively dissolve alumina while having almost no chemical reaction with the carbon nanotubes themselves. However, if too high a concentration of acid and / or base is used, it will damage the carbon nanotubes.
[0051] In some embodiments, the etching process is further included after completion and before obtaining the positive carbon nanotubes, including washing and drying the carbon nanotubes;
[0052] In some embodiments, the carbon deposition in step (4) is performed using the CVD method.
[0053] In some embodiments, the flow rate of the carbon source gas during the carbon deposition process in step (4) is 10 sccm-100 sccm, for example, it can be 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, 60 sccm, 70 sccm, 80 sccm, 90 sccm or 100 sccm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0054] In some embodiments, the carbon deposition temperature in step (4) is 400℃-800℃, for example, it can be 400℃, 420℃, 450℃, 480℃, 500℃, 520℃, 550℃, 580℃, 600℃, 620℃, 650℃, 700℃, 750℃, 780℃ or 800℃, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0055] As a preferred embodiment of the preparation method of the present invention, the preparation method includes the following steps:
[0056] (1) Growth of arrayed carbon nanotubes: A double-ended alumina template with a pore diameter of 10nm-20nm and a thickness of 5μm-25μm with open ends is heated to the first reaction temperature of 600℃-900℃ under an inert atmosphere, and then carbon source gas is introduced at a flow rate of 10sccm-100sccm. The first reaction lasts for 10min-60min, and an alumina template with arrayed carbon nanotubes grown inside the tube is obtained.
[0057] (2) Opening of arrayed carbon nanotubes: The alumina template with arrayed carbon nanotubes growing inside the tube is heated in air at 300℃-450℃ for 1h-3h to obtain open carbon nanotubes.
[0058] (3) Alumina template removal: The open carbon nanotubes are placed in the etching solution to etch and remove the alumina template. After washing and drying, the positive carbon nanotubes are obtained.
[0059] (4) Silicon deposition: Silicon nanoparticles are deposited into the interior of positive carbon nanotubes using a gas phase method and / or a liquid phase method to obtain carbon nanotubes with deposited silicon.
[0060] The gas phase method specifically includes the following steps: the positive carbon nanotubes are heated to the second reaction temperature of 450℃-700℃ under an inert atmosphere, and then silicon source gas is introduced at a flow rate of 5sccm-100sccm. The second reaction lasts for 5min-30min to obtain carbon nanotubes with deposited silicon.
[0061] The liquid phase method specifically includes the following steps: mixing the positive carbon nanotubes and the silicon source liquid at a ratio of 5wt.%-30wt.% of silicon source liquid to positive carbon nanotubes, performing ultrasonic impregnation, and then pyrolyzing at 300℃-500℃ to obtain carbon nanotubes with deposited silicon.
[0062] (5) Carbon layer encapsulation: The silicon source gas is stopped from being introduced into the carbon nanotubes deposited with silicon, and carbon source gas is introduced. Carbon is deposited at both ends of the carbon nanotubes deposited with silicon by CVD at 400℃-800℃ to obtain the composite anode material of nano-silicon confined by the carbon nanotubes.
[0063] This invention effectively addresses the technical challenge of easy agglomeration of nano-silicon particles by controlling the length of carbon nanotubes and the deposition rate of silane gas. It ensures that silicon particles are uniformly distributed inside the carbon nanotubes, thereby avoiding the risk of structural failure caused by local volume expansion and concentration, and significantly improving the structural stability and cycle life of the material.
[0064] In a second aspect, the present invention provides a composite anode material of carbon nanotube-confined encapsulated silicon nanoparticles, which is prepared according to the preparation method described in the first aspect; the composite anode material of carbon nanotube-confined encapsulated silicon nanoparticles includes carbon nanotubes and silicon nanoparticles located inside the carbon nanotubes.
[0065] The median particle size of the nano-silicon particles is 5nm-50nm, for example, it can be 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm or 50nm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0066] The length of the carbon nanotubes is 5μm-20μm, for example, it can be 5μm, 8μm, 10μm, 12μm, 15μm, 18μm or 20μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0067] This invention further controls the length of carbon nanotubes to 5μm-20μm. Excessively long carbon nanotubes will increase the diffusion resistance of silane molecules, resulting in uneven distribution of silane molecules inside the tube, causing uneven deposition of nano-silicon, with thick deposition at the tube opening and thin or even none inside; excessively short carbon nanotubes will limit the total volume and surface area of the material, thereby reducing the silicon loading.
[0068] The inner diameter of the carbon nanotube is 10nm-20nm, for example, it can be 10nm, 12nm, 15nm, 18nm or 20nm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0069] This invention further controls the inner diameter of carbon nanotubes to 10nm-20nm. If the inner diameter is too small, silane molecules may not be able to enter or may quickly block the opening. If the inner diameter is too large, it may reduce the specific surface area and affect the mechanical and electrical properties of the carbon nanotubes themselves.
[0070] The wall thickness of the carbon nanotubes is 3 to 8 layers, for example, 3, 4, 5, 6, 7 or 8 layers, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0071] This invention further controls the wall thickness of carbon nanotubes to 3-8 layers. Multilayer carbon nanotubes significantly reduce the inner diameter, directly limiting the silicon content. Although single-layer carbon nanotubes have a large specific surface area, their structural strength is relatively weak, and they are prone to collapse during deposition or application.
[0072] The composite anode material of carbon nanotube confined encapsulated silicon nanotubes provided by this invention encapsulates silicon nanotubes within the inner cavity of carbon nanotubes, synergistically solving the two core problems of silicon volume expansion and poor conductivity at the structural level. It can both limit the volume expansion of silicon nanotubes and provide an efficient electron transport channel, significantly improving the application reliability of the composite structure.
[0073] Thirdly, the present invention provides a negative electrode sheet, the negative electrode sheet comprising the composite negative electrode of carbon nanotube confined and encapsulated nano-silicon as described in the second aspect.
[0074] Fourthly, the present invention provides a secondary battery, the secondary battery comprising the negative electrode sheet described in the third aspect.
[0075] The secondary battery provided by this invention has excellent mechanical properties, high energy density, low volume expansion and long cycle life, and has broad application prospects.
[0076] The numerical range described in this invention includes not only the point values listed above, but also any point values within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values included in the range.
[0077] Compared with the prior art, the present invention has at least the following beneficial effects:
[0078] (1) The composite anode material of carbon nanotube confined encapsulation of nano-silicon provided by the present invention uses a variety of deposition techniques to deposit and encapsulate nano-silicon particles in the internal cavity of carbon nanotubes, thereby achieving uniform deposition and tight encapsulation of nano-silicon particles in the internal cavity of carbon nanotubes. This fundamentally changes the composite method of silicon and carbon nanotubes, making full use of the internal cavity of carbon nanotubes to buffer the volume expansion of silicon particles and avoid silicon particle pulverization and electrode structure damage.
[0079] (2) The composite anode material of carbon nanotube confined encapsulation of nano-silicon provided by the present invention encapsulates nano-silicon in the inner cavity of carbon nanotube, and solves the two core problems of silicon volume expansion and poor conductivity from the structural level. It can not only limit the volume expansion of nano-silicon, but also provide an efficient electron transport channel, significantly improving the application reliability of the composite structure.
[0080] (3) The secondary battery provided by the present invention has excellent mechanical properties, high energy density, low volume expansion and long cycle life, and has broad application prospects. Attached Figure Description
[0081] Figure 1 This is a schematic diagram of the structure of the composite anode material of carbon nanotube confined and encapsulated nano-silicon obtained in Example 1 of the present invention;
[0082] Figure 2 This is a schematic diagram of the structure of the double-pass alumina template used in Embodiment 1 of the present invention. Detailed Implementation
[0083] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0084] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values 1 and 2 are listed, and the maximum range values 3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.
[0085] In this invention, "a combination of at least two" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or a combination of at least two" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention. In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this invention, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.
[0086] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various locations throughout the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this invention can be combined with other embodiments that do not conflict with the technology. The ordinal numbers "first," "second," "third," and "fourth," etc., used in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect" in this invention are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.
[0087] In this invention, the order in which the steps are written in the methods described in each embodiment does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.
[0088] Unless otherwise specified, all reagents and consumables used in the following examples and comparative examples were purchased from conventional reagent manufacturers in the art; unless otherwise specified, the experimental methods and techniques used were conventional methods and techniques in the art.
[0089] Example 1
[0090] This embodiment provides a method for preparing a composite anode material with carbon nanotube confinement and encapsulation of nano-silicon, the preparation method comprising the following steps:
[0091] (1) Growth of arrayed carbon nanotubes: A double-ended alumina template with a pore diameter of 15 nm and a thickness of 12 μm with open ends was placed in a CVD furnace. High-purity argon gas was first introduced to purge the residual gas in the furnace. The temperature was raised to the first reaction temperature of 750 °C. Then, methane gas was introduced at a flow rate of 50 sccm. The first reaction was carried out for 30 min to obtain an alumina template with arrayed carbon nanotubes growing inside the tube.
[0092] (2) Opening of arrayed carbon nanotubes: The alumina template with arrayed carbon nanotubes growing inside the tube is heated in air at 350°C for 2 hours to obtain open carbon nanotubes.
[0093] (3) Removal of alumina template: The open carbon nanotubes were placed in a 0.1 mol / L sodium hydroxide solution to etch and remove the alumina template. After washing and drying, the positive carbon nanotubes were obtained.
[0094] (4) Vapor phase silicon deposition: In the CVD furnace, carbon nanotubes are placed along the direction of silane gas flow. High-purity argon gas is first introduced to purge the residual gas in the furnace. The temperature is raised to the second reaction temperature of 450°C. Then, silane gas is introduced at a flow rate of 50 sccm. The second reaction is carried out for 20 min to obtain carbon nanotubes with deposited silicon. The silicon source gas includes silane gas and argon gas with a volume ratio of 20:80.
[0095] (5) Carbon layer encapsulation: Silicate gas is stopped from being introduced into the carbon nanotubes with deposited silicon, and acetylene gas is introduced at a flow rate of 20 sccm. Carbon is deposited at both ends of the carbon nanotubes with deposited silicon by CVD at 550℃ to obtain the composite anode material of nano-silicon confined by the carbon nanotubes.
[0096] A schematic diagram of the prepared composite anode material of carbon nanotube confined and encapsulated nano-silicon is shown below. Figure 1 As shown, from Figure 1 As can be seen in the figure, the yellow spheres represent silicon nanoparticles, and the outer layer is carbon nanotubes. The silicon nanoparticles are filled inside the nanotubes, thereby using the excellent mechanical properties of carbon nanotubes to solve the problems of electrode pulverization and structural collapse caused by the huge volume effect of silicon during lithium insertion and extraction. At the same time, the excellent conductivity of carbon nanotubes is used to improve the rate performance degradation caused by the low intrinsic conductivity of silicon, thereby achieving stable cycling of high-capacity silicon-based anodes.
[0097] The structural diagram of the double-channel alumina template used in step (1) is shown below. Figure 2As shown, the alumina templates all have uniform pores and are open at both ends, allowing carbon source gas to be continuously introduced and grow arrays of carbon nanotubes on the sidewalls.
[0098] Example 2
[0099] This embodiment provides a method for preparing a composite anode material with carbon nanotube confinement and encapsulation of nano-silicon, the preparation method comprising the following steps:
[0100] (1) Growth of arrayed carbon nanotubes: A double-ended alumina template with a pore diameter of 13 nm and a thickness of 6 μm with open ends was placed in a CVD furnace. High-purity argon gas was first introduced to purge the residual gas in the furnace. The temperature was raised to the first reaction temperature of 650 °C. Then, methane gas was introduced at a flow rate of 30 sccm. The first reaction was carried out for 50 min to obtain an alumina template with arrayed carbon nanotubes growing inside the tube.
[0101] (2) Opening of arrayed carbon nanotubes: The alumina template with arrayed carbon nanotubes growing inside the tube is heated in air at 300°C for 2.5 h to obtain open carbon nanotubes.
[0102] (3) Removal of alumina template: The open carbon nanotubes were placed in a 0.1 mol / L sodium hydroxide solution to etch and remove the alumina template. After washing and drying, the positive carbon nanotubes were obtained.
[0103] (4) Liquid phase silicon deposition: mix normal carbon nanotubes and phenyltriethoxysilane at 10 wt.% of the normal carbon nanotubes, perform ultrasonic impregnation, and then pyrolyze at 400 °C to obtain carbon nanotubes with deposited silicon.
[0104] (5) Carbon layer encapsulation: The carbon nanotubes with deposited silicon are placed in a CVD furnace and acetylene gas is introduced. Carbon is deposited on both ends of the carbon nanotubes with deposited silicon at 650°C by CVD method to obtain the composite anode material of nano-silicon confined by the carbon nanotubes.
[0105] Example 3
[0106] This embodiment provides a method for preparing a composite anode material with carbon nanotube confinement and encapsulation of nano-silicon, the preparation method comprising the following steps:
[0107] (1) Growth of arrayed carbon nanotubes: A double-ended alumina template with a pore diameter of 18 nm and a thickness of 20 μm with open ends was placed in a CVD furnace. High-purity argon gas was first introduced to purge the residual gas in the furnace. The temperature was raised to the first reaction temperature of 650 °C. Then, acetylene gas was introduced at a flow rate of 80 sccm. The first reaction was carried out for 20 min to obtain an alumina template with arrayed carbon nanotubes growing inside the tube.
[0108] (2) Opening of arrayed carbon nanotubes: The alumina template with arrayed carbon nanotubes growing inside the tube is heated in air at 400°C for 1 hour to obtain open carbon nanotubes.
[0109] (3) Alumina template removal: The open carbon nanotubes were placed in a 25% hydrochloric acid solution to etch and remove the alumina template. After washing and drying, the positive carbon nanotubes were obtained.
[0110] (4) Vapor phase silicon deposition: In the CVD furnace, carbon nanotubes are placed along the direction of silane gas flow. High-purity argon gas is first introduced to purge the residual gas in the furnace. The temperature is raised to the second reaction temperature of 500°C. Then, methylsilane gas is introduced at a flow rate of 80 sccm. The second reaction is carried out for 20 min to obtain carbon nanotubes with deposited silicon. The silicon source gas includes methylsilane gas and argon gas with a volume ratio of 10:90.
[0111] (5) Carbon layer encapsulation: Methylsilane gas is stopped from being introduced into the carbon nanotubes deposited with silicon, and methane gas is introduced. Carbon is deposited at both ends of the carbon nanotubes deposited with silicon by CVD at 700°C to obtain the composite anode material of nano-silicon confined by the carbon nanotubes.
[0112] Example 4
[0113] This embodiment provides a method for preparing a composite negative electrode material of carbon nanotube confined encapsulated nano-silicon. The only difference from Embodiment 1 is that the pore diameter of the alumina template in step (1) is 5 nm, while the other steps remain unchanged.
[0114] Example 5
[0115] This embodiment provides a method for preparing a composite negative electrode material of carbon nanotube confined encapsulated nano-silicon. The only difference from Embodiment 1 is that the length of the alumina template in step (1) is 30 μm, while the other steps remain unchanged.
[0116] Example 6
[0117] This embodiment provides a method for preparing a composite anode material of carbon nanotube confined encapsulated nano-silicon. The only difference from Embodiment 1 is that the flow rate of the silicon source gas in step (4) is 200 sccm, while the other steps remain unchanged.
[0118] Example 7
[0119] This embodiment provides a method for preparing a composite anode material of carbon nanotube confined encapsulated nano-silicon. The only difference from Embodiment 1 is that the silicon source gas in step (4) includes silane gas and inert gas in a volume ratio of 60:40, while the other steps remain unchanged.
[0120] Example 8
[0121] This embodiment provides a method for preparing a composite negative electrode material of carbon nanotube confinement encapsulation of nano-silicon. The only difference from Embodiment 2 is that the mass of the silicon source liquid in step (4) accounts for 2 wt.% of the positive carbon nanotubes, while the other steps remain unchanged.
[0122] Example 9
[0123] This embodiment provides a method for preparing a composite negative electrode material of carbon nanotube confinement encapsulation of nano-silicon. The only difference from Embodiment 2 is that the mass of the silicon source liquid in step (4) accounts for 40 wt.% of the positive carbon nanotubes, while the other steps remain unchanged.
[0124] Comparative Example 1
[0125] This comparative example provides a silicon-carbon composite anode material, which differs from Example 1 only in that the nano-silicon particles and carbon nanotubes are simply mechanically mixed at a mass ratio of 1:4.
[0126] Comparative Example 2
[0127] This comparative example provides a silicon-carbon composite anode material, which is prepared by the following method:
[0128] (1) Carbonization: First, the phenolic resin is placed in a tube furnace and heated to 900°C under an argon atmosphere. It is then kept at that temperature for 2 hours to obtain carbonized phenolic resin.
[0129] (2) Activation and pore formation: KOH and the phenolic resin carbon obtained in step (1) are ground and mixed in a mass ratio of 3:1, placed in a tube furnace, heated to 750°C under an argon atmosphere, and kept at that temperature for 2 hours;
[0130] (3) Acid washing: The mixture obtained in step (2) is placed in 0.1M dilute hydrochloric acid and magnetically stirred at 80°C for 3 hours. After filtration, washing with water until neutral, and drying, phenolic resin-based porous carbon is obtained.
[0131] (4) Vapor phase silicon deposition: consistent with step (4) of Example 1;
[0132] (5) Carbon coating: Same as step (5) in Example 1.
[0133] Application Example 1
[0134] This application example provides a negative electrode sheet, which is prepared by the following method:
[0135] The composite anode material of carbon nanotube-encapsulated nano-silicon from Example 1, carbon black, CMC, and SBR were dispersed in deionized water at a mass ratio of 80:10:5:5. The mixture was stirred at 2000 r / min to obtain an anode slurry with a solid content of 40%. The anode slurry was coated onto copper foil, dried, rolled, and cut into circular electrode sheets with a diameter of 14 mm and an areal density of 8 mg / cm³. 2 .
[0136] Application Examples 2-9
[0137] Application Examples 2-9 each provide a negative electrode sheet. The only difference from Application Example 1 is that, when preparing the negative electrode sheet, the composite negative electrode material of carbon nanotube confined encapsulated nano-silicon in Example 1 is replaced with the composite negative electrode material of carbon nanotube confined encapsulated nano-silicon in Examples 2-9.
[0138] Comparative Application Example 1 - Comparative Application Example 2
[0139] Comparative Application Examples 1 and 2 each provide a negative electrode sheet. The only difference from Application Example 1 is that, when preparing the negative electrode sheet, the composite negative electrode material of carbon nanotube confined and encapsulated nano-silicon in Example 1 is replaced with the silicon-carbon composite negative electrode material in Comparative Examples 1 and 2.
[0140] test:
[0141] The negative electrode sheets prepared in the corresponding use cases and comparative application examples were assembled into button half-cells for testing. The test results are shown in Table 1 below.
[0142] The counter electrode of a coin cell is a lithium metal sheet.
[0143] The electrolyte is: 1 mol / L LiPF6 dissolved in EC / EMCC at a volume ratio of 1:1;
[0144] The test conditions were: 0.1C charge-discharge cycle was performed using a blue electric current tester, where 1C = 3750mAh / g.
[0145] Table 1
[0146]
[0147] The test results show that:
[0148] (1) As can be seen from Application Examples 1-3, this invention uses various deposition techniques to deposit and encapsulate nano-silicon particles within the internal cavity of carbon nanotubes, achieving uniform deposition and tight encapsulation of nano-silicon particles within the internal cavity of carbon nanotubes. This fundamentally changes the silicon-carbon nanotube composite method, fully utilizing the internal cavity of the carbon nanotubes to buffer the volume expansion of silicon particles and avoid silicon particle pulverization and electrode structure damage. This significantly improves the mechanical properties, energy density, and long-cycle stability of the secondary battery.
[0149] (2) By comparing application example 1 with application examples 4-5, it can be seen that the present invention further controls the pore diameter of the alumina template to 10nm-20nm and the thickness to 5μm-25μm, thereby constructing positive carbon nanotubes with higher diameter and corresponding length. If the pore diameter of the alumina template is too small, the inner diameter of the prepared positive carbon nanotubes will be too small, which will further prevent silane molecules from entering or quickly block the tube opening, which is not conducive to silicon deposition. If the thickness of the alumina template is too thick, the prepared positive carbon nanotubes will be too long. The excessively long carbon nanotubes will increase the diffusion resistance of silane molecules, resulting in uneven distribution of silane molecules in the tube, causing uneven deposition of nano-silicon, with thick deposition at the tube opening and thin or even none inside.
[0150] (3) By comparing application example 1 with application examples 6-7, it can be seen that by further controlling the flow rate of silicon source gas to 5 sccm-100 sccm and the volume ratio of silane gas to inert gas to (5-50):(95-50), the present invention can achieve better silicon deposition efficiency and make silicon particles uniformly dispersed inside the positive carbon nanotubes. If the flow rate is too fast or the proportion of silane gas is too large, it will lead to the aggregation and blockage of nano-silicon particles, thereby affecting the uniformity of nano-silicon distribution and ultimately causing structural damage to carbon nanotubes during charging and discharging.
[0151] (4) By comparing Application Example 1 with Application Examples 8-9, it can be seen that the present invention further controls the mass of silicon source liquid to be 5wt.%-30wt.% of positive carbon nanotubes. The mass ratio of silicon source liquid affects the loading of silicon and the uniformity of dispersion in carbon nanotubes. If the mass of silicon source liquid is too large, the excessive silicon deposition will produce a huge volume effect, which will fall off from the surface of carbon nanotubes during charging and discharging, resulting in a decrease in cycle stability. If the mass of silicon source liquid is too small, the loading of nano-silicon will be significantly insufficient, and the charging specific capacity will not reach the expected target.
[0152] (5) As can be seen from Application Example 1 and Comparative Application Example 1-Comparative Application Example 2, compared with the silicon-carbon composite anode prepared by the traditional method, the phenolic resin-based porous carbon prepared by it has poor strength and toughness and does not have the excellent mechanical properties of carbon nanotubes. Therefore, it cannot achieve the technical effect of restricting the repeated expansion and contraction of nano-silicon.
[0153] In summary, the composite anode material of carbon nanotube-encapsulated silicon nanoparticles provided by this invention employs various deposition techniques to deposit and encapsulate silicon nanoparticles within the internal cavity of carbon nanotubes. This achieves uniform deposition and tight encapsulation of silicon nanoparticles within the internal cavity of carbon nanotubes, fundamentally changing the silicon-carbon nanotube composite method. It fully utilizes the internal cavity of carbon nanotubes to buffer the volume expansion of silicon particles, avoiding silicon particle pulverization and electrode structure damage.
[0154] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a composite anode material of carbon nanotube-encapsulated nano-silicon, characterized in that, The preparation method includes the following steps: (1) The double-pass alumina template is heated to the first reaction temperature under an inert atmosphere, and then carbon source gas is introduced to carry out the first reaction, so as to obtain an alumina template with arrayed carbon nanotubes grown inside the tube. (2) Heating an alumina template with arrayed carbon nanotubes growing inside the tube to obtain open carbon nanotubes; (3) Place the open carbon nanotubes in the etching solution and etch away the alumina template to obtain the positive carbon nanotubes; (4) Silicon nanoparticles are deposited into the interior of positive carbon nanotubes by gas-phase method and / or liquid-phase method to obtain carbon nanotubes with deposited silicon; (5) Carbon source gas is introduced into the carbon nanotubes containing silicon to perform carbon deposition, thereby obtaining the composite anode material of nano-silicon confined by the carbon nanotubes.
2. The preparation method according to claim 1, characterized in that, Step (4) of the gas phase method specifically includes the following steps: The carbon nanotubes are heated to the second reaction temperature under an inert atmosphere, and then a silicon source gas is introduced to carry out the second reaction, resulting in carbon nanotubes with deposited silicon.
3. The preparation method according to claim 2, characterized in that, In step (4), the second reaction temperature is 450℃-700℃; And / or, the silicon source gas comprises silane gas and inert gas in a volume ratio of (5-50):(95-50); And / or, the silane gas includes any one or a combination of at least two of silane, disilane, methylsilane or trichlorosilane; And / or, the flow rate of the silicon source gas is 5 sccm-100 sccm; And / or, the second reaction takes 5 min to 30 min.
4. The preparation method according to any one of claims 1-3, characterized in that, Step (4) of the liquid phase method specifically includes the following steps: Mixing positive carbon nanotubes and silicon source liquid, ultrasonically impregnating them, and then pyrolyzing them at 300℃-500℃, yields carbon nanotubes with deposited silicon. The silicon source liquid includes any one or a combination of at least two of cyclopentylsilane, polysilane, silicon tetrachloride, phenyltriethoxysilane, methyl orthosilicate, or alkoxysilane; The mass of the silicon source liquid accounts for 5 wt.%-30 wt.% of the positive carbon nanotubes.
5. The preparation method according to any one of claims 1-4, characterized in that, The double-channel alumina template in step (1) has channels with a diameter of 10nm-20nm and a thickness of 5μm-25μm. And / or, the first reaction temperature is 600℃-900℃; And / or, the inert atmosphere includes high-purity nitrogen and / or argon; And / or, the carbon source gas includes any one or a combination of at least two of acetylene, ethylene, methane or toluene vapor; And / or, the flow rate of the carbon source gas is 10 sccm-100 sccm; And / or, the time for the first reaction is 10 min to 60 min.
6. The preparation method according to any one of claims 1-5, characterized in that, The heating temperature in step (2) is 300℃-450℃; And / or, the heating time is 1h-3h; And / or, the heating atmosphere is an oxygen-containing atmosphere.
7. The preparation method according to any one of claims 1-6, characterized in that, The etching solution in step (3) includes an acid solution or an alkaline solution; And / or, the acid solution includes hydrochloric acid solution and / or sulfuric acid solution, and the alkaline solution includes sodium hydroxide solution; And / or, the carbon deposition in step (4) is performed using CVD; And / or, the flow rate of the carbon source gas during the carbon deposition process in step (4) is 10 sccm-100 sccm; And / or, the carbon deposition temperature in step (4) is 400℃-800℃.
8. A composite anode material of carbon nanotube-encapsulated nano-silicon, characterized in that, The composite anode material of carbon nanotube confined encapsulated nano-silicon is prepared by the preparation method according to any one of claims 1-7; The composite anode material of carbon nanotube confinement encapsulation of nano-silicon includes carbon nanotubes and nano-silicon particles located inside the carbon nanotubes. The median particle size of the silicon nanoparticles is 5nm-50nm.
9. A negative electrode sheet, characterized in that, The negative electrode comprises the composite negative electrode of carbon nanotube confined encapsulated nano-silicon as described in claim 8.
10. A secondary battery, characterized in that, The secondary battery includes the negative electrode sheet as described in claim 9.
Citation Information
Patent Citations
Silicon-carbon-carbon nanotube composite negative electrode material and preparation method and application thereof
CN113860288A
Silicon-carbon-based composite material, preparation method thereof and application of silicon-carbon-based composite material in lithium ion battery
CN120518058A
